2014
DOI: 10.1080/02640414.2014.946951
|View full text |Cite
|
Sign up to set email alerts
|

The movement of the trunk and breast during front crawl and breaststroke swimming

Abstract: Breast displacement has been investigated in various activities to inform bra design, with the goal of minimising movement; however, breast motion during swimming has yet to be considered. The aim was to investigate trunk and breast kinematics whilst wearing varying levels of breast support during two swimming strokes. Six larger-breasted females swam front crawl and breaststroke (in a swimming flume), in three breast support conditions while three video cameras recorded the motion of the trunk and right breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Furthermore, no published research was located that compared the magnitude of breast movement displayed by older women and younger women with the same breast volume. Although the magnitude of breast movement has been reported to increase with breast size, only a few of the published studies have included women with bra sizes equivalent to a DD cup or larger (15,89,101,107,108,160,166). This is despite bra cup sizes ranging from A up to a size I cup (147), whereby 37% of the female population have large or hypertrophic breasts (27).…”
Section: Figure 3 Perimeter Of the Breast And Its Attachments To The Anterior-lateral Chest Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, no published research was located that compared the magnitude of breast movement displayed by older women and younger women with the same breast volume. Although the magnitude of breast movement has been reported to increase with breast size, only a few of the published studies have included women with bra sizes equivalent to a DD cup or larger (15,89,101,107,108,160,166). This is despite bra cup sizes ranging from A up to a size I cup (147), whereby 37% of the female population have large or hypertrophic breasts (27).…”
Section: Figure 3 Perimeter Of the Breast And Its Attachments To The Anterior-lateral Chest Wallmentioning
confidence: 99%
“…Furthermore, most studies have investigated breast motion during walking or running. Less than a quarter of published studies have examined breast motion during other exercise modalities, such as aquatic-based activities (97,106,107), jumping (15,25,84,86,106,116,132,160), and upper limb movements (160). Further research is therefore required to investigate breast motion of more women, particularly those who are older, have larger breasts, and represent the body mass index of the broader female population.…”
Section: Figure 3 Perimeter Of the Breast And Its Attachments To The Anterior-lateral Chest Wallmentioning
confidence: 99%
“…It was reported that 63% of women in a China cohort had breast pain symptoms, of which 35% believed that exercise was one of the causes of breast pain [4]. Fortunately, increasing the level of breast support (wearing a bra, especially a sports bra) has been repeatedly linked to reduced breast displacement [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that understanding breast motion during one kind of exercise is helpful to inform sports bra design and thus alleviates breast discomfort during this kind of exercise [5]. Previous research has found differences in breast motion during a range of exercise modalities, including walking [9], running [10] and jumping [11].…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Fortunately, breast displacement could be reduced by wearing sports bras. [8][9][10] Previous researches have investigated breast biomechanics during a range of exercise modalities, including treadmill walking [11], running [12] and swimming, [13] and found that increases in breast support (wearing bra) caused decreases in breast displacement. [13] But up to now, much less exploration on the vertical breast displacement during rope skipping was found.…”
Section: Introductionmentioning
confidence: 99%